Penerapan Manajemen Risiko Pada Salon Nusa Bunga Maumere - Kristiana Reinaldis Aek; Maria Ercytasi B. Lein; Florensia Emiliana; Maria Wihelmina Susanti; Agnes Silvania Dua Sareng (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
Beauty salons are part of the growing creative services industry, yet they face various risks that can disrupt business continuity. This study aims to identify the types of risks, their causes, impacts, challenges, management strategies, and risk monitoring methods implemented by Nusa Bunga Salon in Maumere. The methods used included interviews, direct observation, and documentation. The results indicate that the salon faces operational, financial, marketing, and reputational risks. These risks are caused by factors such as inadequate employee skills, unstable income, intense competition, and customer complaints, which can result in service disruptions, decreased service quality, reduced customer numbers, and decreased revenue. Key challenges include an unstrategic location, limited workforce, fluctuating customer numbers, and rising material prices. To address these challenges, the salon implemented strategies such as home visits, utilization of social media, regulated employee working hours, and improved service quality. Risk monitoring is carried out continuously through operational supervision, customer satisfaction evaluations, inventory checks, and financial records. It was concluded that implementing sound risk management is crucial for maintaining business continuity. Therefore, it is recommended that salons continuously improve the quality of their human resources, financial management, marketing strategies, and service innovation